2016
DOI: 10.2147/ppa.s108391
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial to test the effectiveness of a glaucoma patient navigator to improve appointment adherence

Abstract: PurposePatients with glaucoma who do not keep their follow-up eye care appointments are at risk for developing more severe ocular disease. The primary aim of the current study was to evaluate whether the use of a patient navigator altered adherence to follow-up eye care appointments in community-versus office-based settings.Patients and methodsPatients diagnosed with a glaucoma-related condition following a comprehensive eye examination at 43 community sites in Philadelphia, PA, USA, were enrolled in this pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…'Patient navigators' likely fill a similar role to those who facilitate behavioural activation; they help guide patients through the steps of eyecare, providing support as needed. An initial randomised controlled trial (RCT) evaluating effectiveness of adding patient navigators within an already supportive eyecare programme showed inconclusive results 72 but a follow-up RCT is underway. [73][74][75] Hiring school nurses to help students navigate from screening to full eye exams and comply with treatment was reported to be effective compared with screening alone 76 (although some universal childhood screening programmes were very effective at promoting follow-up).…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…'Patient navigators' likely fill a similar role to those who facilitate behavioural activation; they help guide patients through the steps of eyecare, providing support as needed. An initial randomised controlled trial (RCT) evaluating effectiveness of adding patient navigators within an already supportive eyecare programme showed inconclusive results 72 but a follow-up RCT is underway. [73][74][75] Hiring school nurses to help students navigate from screening to full eye exams and comply with treatment was reported to be effective compared with screening alone 76 (although some universal childhood screening programmes were very effective at promoting follow-up).…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…(d) The PTGDF found that patient navigators and social workers improved timely attendance at the first followup after the confirmatory eye examination (74.4% vs. 39.0%; adjusted risk ratio = 1.85; 95% CI: 1.51-2.28; P < 0.001; data not published). 12,13 These 2 studies identified successful strategies to affordably and effectively screen for treatable eye disease in vulnerable, underserved populations in urban settings. Despite this progress, substantial challenges remain to reduce the burden of vision-threatening conditions in these at-risk populations.…”
Section: Broader Lessons Learnedmentioning
confidence: 99%
“…The PTGDF found that patient navigators and social workers improved timely attendance at the first follow-up after the confirmatory eye examination (74.4% vs. 39.0%; adjusted risk ratio=1.85; 95% CI: 1.51-2.28; P <0.001; data not published) 12,13…”
Section: Broader Lessons Learnedmentioning
confidence: 99%
“…Barriers to nonadherence include health care costs, lack of transportation, and emotional distress (7,8). These barriers most often affect people of color, who have lower attendance rates at follow-up eye care appointments than White patients (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%